What determines financial literacy in Japan? - Yoshihiko Kadoya; Mostafa Saidur Rahim Khan (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This study aims to determine the factors that affect financial literacy in Japan using data from Osaka University's Preference Parameter Study in Japan. We examined fourteen variables covering respondents' demographic, socio-economic, and psychological backgrounds drawn from social learning, consumer socialization, and psychology theories of learning. The results indicate that the demographic factors of gender, age, and education; the socio-economic factors of income and occupation; and the psychological factor of perceptions about future significantly affect the level of financial literacy. We checked the robustness of results using a different measure of financial literacy, which also confirmed our findings. The results emphasize the need for a formal financial education and social contact to boost financial literacy levels in Japan.
Keywords: D14; G02; 330; financial literacy; household; finance